Legal Protection for Substitute Notaries in Civil Court Proceedings - Obrien Kaawoan, Yeremia; Aju Wisnuwardhani, Dyah; Nur Widhiyanti, Hanif (The Islamic Education and Multiculturalism Foundation, 2024)
In carrying out their duties as Substitute Notaries, the obligation to adhere to the law is imperative as stipulated in the legislation, serving as a foundation for fulfilling their responsibilities. According to Article 65 of Law No. 2 of 2014 on the Position of Notary, it is stated that a Notary, Substitute Notary, and Temporary Notary Officer are accountable for every deed they draw up, even after the Notarial Protocol has been handed over or transferred to the custodian of the Notarial Protocol. Therefore, a Substitute Notary must be legally responsible for the deeds they prepare in judicial processes. This is because the deeds created by a Substitute Notary are authentic deeds made by an authorized official and hold evidentiary power in court. In performing their duties as Substitute Notaries in drawing up authentic deeds, there is a possibility of legal issues arising concerning the deeds they create, which may result in the Substitute Notary becoming entangled in legal problems. The Notary Honorary Council (Majelis Kehormatan Notaris) is an institution that exercises authority in providing guidance to Notaries and has the duty to grant approval for Notaries in judicial processes. The obligation to obtain approval from the Notary Honorary Council for Notaries is a form of legal protection for Notaries, as outlined in Article 66 paragraph 1 of the Notary Law. This legal protection is aimed at maintaining the dignity of the Notary profession and safeguarding the interests of the parties involved in legal acts within the deeds. The urgency in this matter lies in Article 66 paragraph 1 of the Notary Law, where the Notary Honorary Council has the authority to grant approval to Investigators, Public Prosecutors, and Judges to conduct examinations and obtain the original deed (Minuta) from the Notary, due to the Notary's obligation to keep the deeds they draw up confidential. To address this issue, a research method is necessary, and the method employed in this research is the Normative Juridical method, which refers to a scientific research method used to find the truth based on the legal logic from a normative perspective.The conclusion drawn from this research is that there is a legal vacuum concerning the regulation of Article 66 paragraph 1 with respect to Substitute Notaries in civil judicial processes.